EFFECTIVITY OF PCNL WITH COMBINED ULTRASOUND AND FLUOROSCOPY - Herwandar, Rajasa; Rochadi, Sungsang (Indonesian Urological Association, 2014)
Objective: To assess the effectiveness of Percutaneous Nephrolithotomy (PCNL) at age > 65 years and its complication. Material & method: Fifty-four patients with renal and proximal ureteral stones who underwent PCNL with ultrasound techniques combined with X-Ray at Sardjito and Pantirapih hospital, during 2007 to 2012. Laboratory data is in the form of hemoglobin, leukocyte count, trombocyte, haematocrit, natrium, potassium, chloride, BUN, creatinine both pre-operative and post-operative. The samples were divided according to age < 65 years old and above. In analyzing categorical data, we used chi-square test, whereas the numeric data analysis is using independent t-test with p < 0.05. Results: We found no significant differences between the age groups < 65 years and age > 65 years in stone location, presence of hydronephrosis, its grade and location. There also no difference based on operative time, intra-operative procedure, its complication and the day of DJ stents removal and nephrostomy. Both group showed similar result on laboratory findings. However, we found that the older age group have 2 days longer in the length of hospitalization than the younger age groups (p = 0.05) and history of diabetes mellitus and hypertension with p < 0.05. Conclusion: PCNL is a safe and effective procedure with minimal complications for the treatment of kidney and proximal ureteral stone, even for patients with co-morbidity. PCNL technique with guidance of ultrasound for early access would help tomake the operating time shorter and less exposure to ionizing radiation.Keywords: Percutaneous nephrolithotomy, age > 65 years old, effectiveness, safety.